Nilai-Nilai Pendidikan Karakter dalam Buku “Saleh Ritual Saleh Sosial” Karya Kh. A. Mustofa Bisri - Muhammad Khoirul Anam; Agus Sutiyono; Ahmad Maghfurin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Character education has always been an important pillar of education in facing various problems. The problem with our education is that we often encounter students who summarize the things they have done, fight, have low respect for parents and teachers, speak impolite words in communication and often use harsh and even dirty words.This study focuses on the values of character education contained in the book